Koser’s Reagent Mediated Oxidation of Aldoximes: Synthesis of Isoxazolines by 1,3-Dipolar Cycloadditions - Budhwan, Rajnish; Rawat, Megha; Peddinti, Rama Krishna (Synthesis, 2023)
A metal- and base-free, robust, and convenient approach for the synthesis of isoxazoline derivatives is reported. This protocol involves 1,3-dipolar cycloaddition between in situ generated nitrile oxides from the corresponding aldoximes using [hydroxy(tosyloxy)iodo]benzene (HTIB, Koser’s reagent) and maleimides, styrene and acrylonitrile. The described methodology is very attractive as it is operationally simple, has broad scope, and does not require any base, metal, or other additives.
Keywords: arylaldoximes; C–C and C–O bond formation; fused isoxazolines; heterocycles; hypervalent iodine; nitrile oxides; oxidation